2018
DOI: 10.1002/anie.201802748
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidative Ruthenium‐Catalyzed C−H/O−H Annulation by Weak O‐Coordination

Abstract: Electrocatalysis has been identified as a powerful strategy for organometallic catalysis, and yet electrocatalytic C-H activation is restricted to strongly N-coordinating directing groups. The first example of electrocatalytic C-H activation by weak O-coordination is presented, in which a versatile ruthenium(II) carboxylate catalyst enables electrooxidative C-H/O-H functionalization for alkyne annulations in the absence of metal oxidants; thereby exploiting sustainable electricity as the sole oxidant. Mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
86
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(90 citation statements)
references
References 97 publications
1
86
0
3
Order By: Relevance
“…After considerable preliminary experimentation, we were pleased to find that the desired product 3aa [14] was best accomplished with asolvent mixture of tAmOH and H 2 O, and KOAc as the additive in au ser-friendly undivided cell setup (entries 1-3). In sharp contrast to rhodium and ruthenium catalysis,the overall efficacycould be considerably improved by the use of p-benzoquinone (BQ) or ferrocene as catalytic redox mediators (entries 4a nd 5), highlighting the beneficial assets of ac ooperative [15] catalysis regime for indirect electrolysis.C ontrol experiments confirmed the essential role of the electricity,c arboxylate additive, [16] and iridium catalyst for the electrooxidative CÀH/CÀHa lkenylation (entries [6][7][8][9][10][11][12]. Notably,hydroquinone (HQ) was likewise identified as efficient redox catalyst for the electrooxidative C À Ha lkenylation (entry 13), while al ess expensive nickel cathode enabled asimilar performance (entry 14).…”
mentioning
confidence: 86%
“…After considerable preliminary experimentation, we were pleased to find that the desired product 3aa [14] was best accomplished with asolvent mixture of tAmOH and H 2 O, and KOAc as the additive in au ser-friendly undivided cell setup (entries 1-3). In sharp contrast to rhodium and ruthenium catalysis,the overall efficacycould be considerably improved by the use of p-benzoquinone (BQ) or ferrocene as catalytic redox mediators (entries 4a nd 5), highlighting the beneficial assets of ac ooperative [15] catalysis regime for indirect electrolysis.C ontrol experiments confirmed the essential role of the electricity,c arboxylate additive, [16] and iridium catalyst for the electrooxidative CÀH/CÀHa lkenylation (entries [6][7][8][9][10][11][12]. Notably,hydroquinone (HQ) was likewise identified as efficient redox catalyst for the electrooxidative C À Ha lkenylation (entry 13), while al ess expensive nickel cathode enabled asimilar performance (entry 14).…”
mentioning
confidence: 86%
“…In contrast, Ackermanna nd co-workers revealed electrochemicala nnulation of benzoica cids with internal alkynes through Ru II -catalyzed CÀHa ctivation (Table 4). [30] As eries of isochromenones were synthesized in good to excellent yields. This procedure was also suitable for heteroaromatic benzoic acid annulation.…”
Section: Anodic Ruthenium-catalyzed Càhb Ond Functionalizationmentioning
confidence: 99%
“…Scope for AnodicR u II -catalyzed annulation of benzoyl acid with alkyne. OPiv = pivalate, GC = glassy carbon [30]. …”
mentioning
confidence: 99%
“…[11] This method uses D 2 O/ T 2 O as a promising strategy to incorporate deuterium or tritium, due to cost efficiency and its user-friendly handling. [12] In sharp [ [13] Within our program on weak chelation assistance for CÀ H activation, [14] mechanistic studies had indicated the potential for a selective isotope incorporation into different structural motifs. Consequentially, we hypothesized that, instead of trapping the ruthenacycle with a carbon source, the use of D 2 O or T 2 O could facilitate the preparation of isotope labeled compounds.…”
mentioning
confidence: 99%